Development of fast release foaming vaginal tablets with clotrimazole. II. The influence of the environmental conditions on preparation and stability - Edit László; Ioan Tomuţă; Sorin E. Leucuţa (Amaltea Medical Publishing House, 2020)
Objectives. The aim of this study was to evaluate the stability over time after storage under normal environmental thermo-hygrometric conditions of immediate release foaming vaginal tablets. Material and methods. 15 formulation of foaming vaginal tablets prepared according with a Box-Bhenken experimental design were packaged in tightly sealed bottles with anhydrous sodium sulphate as desiccant and stored in normal thermo-hygrometric conditions (temperature of 25°C, relative humidity 40-75%). Immediate after preparation, after 1 and 3 months the tablets pharmaceutical characteristics were analysed and modification over time evaluated. Outcomes. The formulation factors studied with experimental design have, in general, the same influence on tablets characteristics after 1 or 3 months storage as immediate after preparation After one month storage in normal thermohygrometric conditions, an increase of the tablets hardness and the foaming time was observed, and a decrease of the volume of the foam, the mass of carbon dioxide released by the foaming. These modifications are accentuated especially by an increased effervescent mixture ratio and not significantly influenced by the other formulation variables. The results obtained after three months storage show that the changes on the tablets characteristics become slower than in the first month. The tablets hardness reaches maximum values after one month, but also there are slower changes regarding the maximum volume of the foam, the resistance of the foam, or the mass of carbon dioxide released after foaming. Low modification was observed for the pH generated in the water, which has a fairly high stability over time, both at one month and after three months storage. Conclusions. Foaming vaginal tablets stored in normal thermo-hygrometric conditions, suffer a sudden modification of their characteristics during the first month of storage, a phenomenon that is due to both the humidity of the environment and the preparation conditions. This modification can be minimized by preparing and storing tablets in low humidity conditions (lower that 10%) or by preparation the formulations with a low effervescent mixture ratio (less than 25%).